Association of Low Serum l-Carnitine Levels with Aortic Stiffness in Patients with Non-Dialysis Chronic Kidney Disease - Hsieh, Yi-Jen (Nutrients, 2020)
l-carnitine (LC) is a co-factor in fatty acid metabolism; its role with respect to aortic stiffness (AS) associated with chronic kidney disease (CKD) was unclear. Our aim was to investigate associations between serum LC levels and AS in patients with non-dialysis CKD stage 3–5. The AS patients were those with carotid-femoral pulse wave velocities (cfPWV) >10 m/s; those with cfPWV ≤10 m/s were included as controls. Serum LC was measured by liquid chromatography and mass spectrometry. Of 136 CKD patients, the 44 (32.4%) with AS were older, exhibited higher rates of diabetes, and had elevated diastolic and systolic blood pressures (SBP), elevated fasting glucose levels and lower levels of serum LC compared to controls. Multivariable logistic regression revealed that serum LC (odds ratio [OR] = 0.949, 95% confidence interval [CI] 0.911–0.988, p = 0.011) and age (OR = 1.055, 95% CI 1.013–1.099, p = 0.009) were independent predictors of AS. Multivariable stepwise linear regression revealed significant positive (age and SBP) and negative (serum LC) correlations with cfPWV. The area under the curve of serum LC as a means to predict AS in CKD patients was 0.657 (95% CI 0.571–0.736, p = 0.0009). We concluded that low serum LC is a significant predictor of AS in patients diagnosed with CKD.